Research on the service quality of emergency medical language services during major unexpected public health events - Xie, Jingyi; Ma, Siyu (Frontiers in Public Health, 2023)
Emergency medical language services (EMLS) have played a crucial role in the COVID-19 pandemic. Research on the quality and its influencing factors of EMLS is necessary. Therefore, this study used the SERVQUAL model to determine factors affecting the quality of EMLS during the pandemic. An online questionnaire was completed by 206 participants who received the service in 2021-2022. Structural Equation Modeling indicated that the service provider and service process significantly influenced the Service Results. In the service process, the evaluation of service content and responsiveness were highly correlated, and both factors significantly affected user satisfaction. In the service provider, tangibility and reliability were highly correlated. The key factors for user willingness to recommend the service were service content and tangibility. It was evident that integrating SERVQUAL model could holistically measure service quality among emergency medical language service providers.